Effect of 6-month fascia-oriented training on jump performance in elite female volleyball players - Vychodilová, R.; Zvonar, M.; Sebera, M. (Studia Sportiva, 2017)
Fascia-oriented training is supposed to enhance physical performance potential. Specifically, the employment of the catapult mechanism, the refinement of the elastic energy storage, remodelling, rehydration and release in fascia tissue are supposed to enable faster and more powerful jump performance. The authors of the present study reviewed that little applied research has been conducted to bring scientific evidence verifying these findings in sports practice. The study was conducted to assess the effect of a 6-month, fascia-oriented training programme, designed in accordance with the principles of the fascia-oriented exercise, on the height of vertical countermovement jump (CMJ) performance in well-trained volleyball players. Sixteen female players (age 17.31 ± 0.98; height 173 ± 5.26; weight 65.25 ± 6.75) competing in the national league were randomly assigned for the training (TG) and control group (CG). TG performed a supervised 25-minute fascia-oriented training twice a week for six months. Measurements were conducted before and after the training intervention; the subjects performed 3 trials of CMJ. The study hypothesized that after the application, the height of CMJ would increase more in TG than in CG. The results show that the height of CMJ in TG increased comparing to CMJ height in CG, though the difference is not statistically significant. The results of the effect size manifest the increase of medium level, by 2.2cm in TG. Thus we conclude that the results of the study indicate that the application of the 6-month, fascia-oriented training aimed to develop the vertical jump performance potential in elite volleyball players is not statistically significantly beneficial.